Novel Bilayer-Shelled N, O-Doped Hollow Porous Carbon Microspheres as High Performance Anode for Potassium-Ion Hybrid Capacitors - Pan, Zhen; Qian, Yong; Li, Yang; Xie, Xiaoning; Lin, Ning; Qian, Yitai (Nano-Micro Letters, 2023)
With the advantages of high energy/power density, long cycling life and low cost, dual-carbon potassium ion hybrid capacitors (PIHCs) have great potential in the field of energy storage. Here, a novel bilayer-shelled N, O-doped hollow porous carbon microspheres (NOHPC) anode has been prepared by a self-template method, which is consisted of a dense thin shell and a hollow porous spherical core. Excitingly, the NOHPC anode possesses a high K-storage capacity of 325.9 mA h g−1 at 0.1 A g−1 and a capacity of 201.1 mAh g−1 at 5 A g−1 after 6000 cycles. In combination with ex situ characterizations and density functional theory calculations, the high reversible capacity has been demonstrated to be attributed to the co-doping of N/O heteroatoms and porous structure improved K+ adsorption and intercalation capabilities, and the stable long-cycling performance originating from the bilayer-shelled hollow porous carbon sphere structure. Meanwhile, the hollow porous activated carbon microspheres (HPAC) cathode with a high specific surface area (1472.65 m2 g−1) deriving from etching NOHPC with KOH, contributing to a high electrochemical adsorption capacity of 71.2 mAh g−1 at 1 A g−1. Notably, the NOHPC//HPAC PIHC delivers a high energy density of 90.1 Wh kg−1 at a power density of 939.6 W kg−1 after 6000 consecutive charge–discharge cycles. Highlights: 1 Proposing a one-step pyrolysis strategy to fabricate a novel bilayer-shelled N, O-doped hollow porous carbon microspheres (NOHPC) anode. 2 The optimized NOHPC anode displays a high K-storage capacity of 325.9 mAh g−1 at 0.1 A g−1 and excellent rate performance (201.1 mAh g−1 at 5 A g−1 after 6000 cycles). 3 The assembled NOHPC//hollow porous activated carbon microspheres (HPAC) potassium ion hybrid capacitors deliver a high energy density of 90.1 Wh kg−1 at a power density of 939.6 W kg−1 even over 6000 cycles.